2007
DOI: 10.1088/0022-3727/40/20/s16
|View full text |Cite
|
Sign up to set email alerts
|

Current status of AlInN layers lattice-matched to GaN for photonics and electronics

Abstract: We report on the current properties of Al1−xInxN (x ≈ 0.18) layers lattice-matched (LM) to GaN and their specific use to realize nearly strain-free structures for photonic and electronic applications. Following a literature survey of the general properties of AlInN layers, structural and optical properties of thin state-of-the-art AlInN layers LM to GaN are described showing that despite improved structural properties these layers are still characterized by a typical background donor concentration of (1–5) × 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
226
0
7

Year Published

2008
2008
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 323 publications
(249 citation statements)
references
References 89 publications
14
226
0
7
Order By: Relevance
“…These experimental results support mixing enthalpy results for relaxed and differently Previous studies of InyAl1-yN show a tendency for random compositional fluctuations during the early stages of growth, which leads to a wavy surface [32], and may explain the higher degree of roughness observed in our ScxAl1-xN/InyAl1-yN samples that is not present in ScxAl1-xN/AlN. In our previous study of ScxAl1-xN thin films, we demonstrated a correlation between columnar microstructure and good crystalline quality [10], suggesting that the columnar microstructure in the present ScxAl1-xN/InyAl1-yN superlattices also indicates an improved crystalline quality.…”
Section: Discussionsupporting
confidence: 88%
“…These experimental results support mixing enthalpy results for relaxed and differently Previous studies of InyAl1-yN show a tendency for random compositional fluctuations during the early stages of growth, which leads to a wavy surface [32], and may explain the higher degree of roughness observed in our ScxAl1-xN/InyAl1-yN samples that is not present in ScxAl1-xN/AlN. In our previous study of ScxAl1-xN thin films, we demonstrated a correlation between columnar microstructure and good crystalline quality [10], suggesting that the columnar microstructure in the present ScxAl1-xN/InyAl1-yN superlattices also indicates an improved crystalline quality.…”
Section: Discussionsupporting
confidence: 88%
“…Furthermore, of these successful results reported in the literature there are only a few reports in terms of the detailed analysis of the transport characteristics of AlInN-based HEMTs. 5,19 In the present work, we investigated and compared the transport properties of high quality AlGaN/AlN/GaN and AlInN/AlN/GaN heterostructures using temperature dependent Hall effect measurements. Analytical models were applied to the experimental results in order to understand the scattering mechanism that governs the performance of devices in a temperature range of 30-300 K. If the scattering mechanisms that are dominant for high-density 2DEGs can be identified, it will guide the modifications to the growth and/or the layer structure that will be necessary to further improve the conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…For example, alloying the two binary nitrides InN and AlN results in the ternary compound Al x In 1-x N, with a bandgap that spans from 0.64 eV to 6.2 eV [2,3]. Al x In 1-x N is particularly attractive since it can be grown lattice matched to GaN and AlGaN [4], ensuring stress-free heterostructures with tunable bandgap [5]. Simultaneously, the constant size reductions of III-nitride device structures are accompanied by a need for increased control and understanding of growth and diffusion mechanisms [6,7] along with accurate compositional and structural information.…”
mentioning
confidence: 99%